Information and Communication Technology Facilities and Services Among Engineering College Libraries in Rayalaseema Region of Andhra Pradesh - Kumar, K. (DESIDOC Journal of Library & Information Technology, 2015)
This article presents information on various ICT facilities and services provided in engineering institutions at Rayalaseema Region of Andhra Pradesh. It addresses current status of institutions providing library services such as traditional, electronic, and document delivery services and facilities like hardware, software and communication resources. Eighty-one completed responses collected with a total response rate of 88.04 %. ANOVA (Analysis of Variance) test was conducted to find out the significance of the variables constituting hardware, software facilities, and communication services versus institutions, respectively. The study showed that 87.65 % library provided with windows XP and 72.84 % Pentium IV workstation. DELNET seems to be the most preferred information network service and VSAT is found to be mostly used communication service. About 60 % libraries are partially automated and barcode technique is most frequently opted for circulation. It is concluded from that automation is still an ongoing process in libraries of Rayalaseem Region. dx.doi.org/10.14429/djlit.35.5.8600